The influence of motivation, organizational commitment and workload on job satisfaction of regional officials with competency as an intervening variable in the Regional Financial and Asset Agency of Riau Islands Province - Ngaliman Ngaliman; Nike Astarina; I Wayan Catrayasa (Goodwood Publishing, 2025)
Purpose: This study aimed to examine the influence of work teams and work environments on organizational loyalty among employees. It specifically explored how teamwork dynamics and workplace conditions contribute to fostering employee loyalty at Hikmah Masamba General Hospital. Research Methodology: A descriptive quantitative approach was employed with a total population of 50 employees, consisting of 26 staff in nursing services and 24 staff in midwifery services. Using a saturated sampling technique, the entire population was included as respondents. Data were collected through structured procedures and analyzed with SPSS version 26, focusing on both partial and simultaneous testing of the independent variables—work team and work environment—on employee loyalty. Results: The results show that both work team and work environment significantly influence organizational loyalty, whether evaluated separately or collectively. These findings highlight that teamwork quality and a supportive environment are critical factors in shaping employee commitment and loyalty within hospital organizations. Conclusions: The study concluded that organizational loyalty is strongly determined by effective teamwork and conducive workplace conditions. Therefore, strengthening collaboration and improving work environments are essential strategies for enhancing loyalty among hospital employees. Limitations: The scope of this research was limited to a single institution, Hikmah Masamba General Hospital, thus restricting the generalizability of its findings to broader contexts. Contribution: This study enriches the literature on organizational loyalty and offers practical insights for healthcare management in developing loyalty through team collaboration and workplace improvements.